RESHAPING INTERCULTURAL COMMUNICATIVE COMPETENCE IN EFL LEARNERS THROUGH AI-MEDIATED LANGUAGE PRODUCTION AND ADAPTIVE FEEDBACK MECHANISMS - Ratna Andhika Mahaputri; Nor Syamimi Iliani Che Hassan (English Review: Journal of English Education, 2026)
Abstract: The integration of artificial intelligence (AI) into English as a Foreign Language (EFL) education has brought about transformative changes in how learners develop intercultural communicative competence (ICC). This systematic literature review examines how AI-mediated language production and adaptive feedback mechanisms reshape ICC among EFL learners. Following PRISMA guidelines, this study analysed 35 peer-reviewed articles published between 2020 and 2025. The review focuses on ELT-relevant dimensions, including automated writing evaluation, generative AI in language learning, and AI-mediated cross-cultural exchange. Findings indicate that AI facilitates ICC by providing real-time adaptive feedback that helps learners negotiate cultural nuances and linguistic norms. The study concludes that AI serves as a "cultural mediator," offering a triadic interaction model that enhances learners' knowledge, skills, and attitudes in intercultural settings.